2004
DOI: 10.1159/000077521
|View full text |Cite
|
Sign up to set email alerts
|

mBAND: a high resolution multicolor banding technique for the detection of complex intrachromosomal aberrations

Abstract: Precise breakpoint definition of chromosomal rearrangements using conventional banding techniques often fails, especially when more than two breakpoints are involved. The classic banding procedure results in a pattern of alternating light and dark bands. Hence, in banded chromosomes a specific chromosomal band is rather identified by the surrounding banding pattern than by its own specific morphology. In chromosomal rearrangements the original pattern is altered and therefore the unequivocal determination of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…Patsalis et al [2004] studied 20 families with apparently balanced translocations and found additional, cryptic aberrations in 15%, which reclassified them as CCRs. This probably also holds true for intrachromosomal rearrangements, but to date, only 10 cases have been described [Romain et al, 1985;Tuck-Muller et al, 1996;Van Esch et al, 2002;Weise et al, 2003;Chudoba et al, 2004;Shim et al, 2004;de Vries et al, 2005;Gajecka et al, 2006;Piovani et al, 2006;Thienpont et al, 2006]. We here report on the detailed characterization of an extremely complex intrachromosomal rearrangement of chromosome 1, revealing 14 different breakpoints, 12 on the p-and two on the q-arm as well as a small deletion of 0.5 Mb on the p-arm.…”
mentioning
confidence: 67%
“…Patsalis et al [2004] studied 20 families with apparently balanced translocations and found additional, cryptic aberrations in 15%, which reclassified them as CCRs. This probably also holds true for intrachromosomal rearrangements, but to date, only 10 cases have been described [Romain et al, 1985;Tuck-Muller et al, 1996;Van Esch et al, 2002;Weise et al, 2003;Chudoba et al, 2004;Shim et al, 2004;de Vries et al, 2005;Gajecka et al, 2006;Piovani et al, 2006;Thienpont et al, 2006]. We here report on the detailed characterization of an extremely complex intrachromosomal rearrangement of chromosome 1, revealing 14 different breakpoints, 12 on the p-and two on the q-arm as well as a small deletion of 0.5 Mb on the p-arm.…”
mentioning
confidence: 67%
“…mBAND was performed on chromosome 20 using a chromosome 20-specific probe kit (XCyte 20, Metasystem), which consists of a mixture of partly overlapping region-specific partial chromosome paints [Chudoba et al, 2004]. Images were captured using a Zeiss Axioplan 2 and analyzed with Metasystem ISIS imaging software.…”
Section: Multicolor High Resolution Banding (Mband)mentioning
confidence: 99%
“…Single chromosomes involved were 2 (Van Esch et al, 2002;Shim et al, 2004), 4 (Romain et al, 1985), 7 (de Vries et al, 2005), 10 (TuckMuller et al, 1996, 16 (Chudoba et al, 2004) and 21 (Weise growth was on the 75th centile for weight and OFC, and on the 75th-90th centile for length. Development was mildly delayed: at age 11 months, his development was 8 months according to the Bayley developmental scale (developmental index of 77), and at age 22 months, development was 16 months.…”
Section: Patient Reportmentioning
confidence: 99%